Peer-to-Peer Lending Syariah dan Dampaknya terhadap Kinerja serta Kesejahteraan Pelaku Usaha Mikro dan Kecil (UMK) pada Masa Pandemi Covid-19 - Harp, Aphylla Planifolia; Resfa Fitri; Yekti Mahanani (Department of Islamic Economics, IPB University, 2021)
Peer-to-Peer (P2P) lending is one of the mechanisms to overcome capital problems for the MSE sector, especially during the Covid-19 pandemic. P2P lending has the highest asset growth compared to other financial technology (fintech) schemes and mostly preferred by the majority of population. As a country with a majority Muslim population, people prefer to use sharia P2P lending, but its role has not been widely documented in the literature. MSEs are business enterprises that contribute greatly to the national gross domestic product (GDP) and absorb the most labor. This study aims to analyze the effect of sharia (P2P) lending on the performance and welfare of MSEs during the Covid-19 pandemic. The method of analysis consists of paired t-test, OLS and logistic regression analysis. Paired t-test results show that there are differences in turnover, profits, operating costs, and the number of MSE workers before and after receiving financing. OLS analysis shows that the amount of financing, business costs, labor, and length of business affect changes in MSE turnover. The results of the logistic regression analysis show that the average family income and the amount of savings significantly affect the welfare of MSE actors.